(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This is it in the article remote education system mother language and literature of teachers qualification increasing his place positive and negative sides in particular the word is conducted. Also the world and Uzbekistan education in the system remote of the system efficiency on the surface it was done studies analysis statement done.